BaFe1−xNixO3 Catalysts for NOx-Assisted Diesel Soot Oxidation - Montilla-Verdú, S.; Torregrosa-Rivero, V.; Díaz-Verde, A.; Illán-Gómez, M. J. (Topics in catalysis, 2023)
In this work, it is analyzed the effect of the partial substitution of Fe by Ni in a BaFeO 3 perovskite to be used as the catalyst for NO x -assisted diesel soot oxidation. A series of BaFe 1−x Ni x O 3 (x = 0, 0.2, 0.4 and 0.8) catalysts have been synthesized by using the sol–gel method. The catalysts have been characterized by ICP-OES, XRD, XPS, O 2 -TPD, H 2 -TPR- and TEM. The catalytic activity for NO to NO 2 oxidation and NO x -assisted diesel soot oxidation have been determined by Temperature Programmed Reaction experiments (NO x -TPR and Soot-NO x -TPR, respectively) and by isothermal reaction at 450 °C. Ni seems not to be inserted in the BaFeO 3 perovskite and, instead of that, BaNiO 3 perovskite and NiO are detected on the surface of the perovskite BaFeO 3 . XPS data reveal the coexistence of Fe(III) and Fe(IV) on the catalyst’s surface (being Fe(III) the main oxidation state) and the presence of oxygen vacancies. All catalysts are active for NO oxidation to NO 2 , showing BaFeO 3 and BaFe 0.6 Ni 0.4 O 3 the best catalytic performance. BaFe 0.6 Ni 0.4 O 3 shows the highest proportion of nickel on surface and it combines the highest activity and stability for NO x -assisted diesel soot oxidation. Also, this catalyst presents the highest initial soot oxidation rate which minimizes the accumulation of unreacted soot during reaction.